Desarrollo de un proceso metodológico para la sostenibilidad en carreteras: Incorporación de residuos plásticos en pavimentos - Sepúlveda Valdez, David Alonso (2025)
The accumulation of plastic waste represents an environmental challenge that affects the construction industry, especially in road paving. In this context, the incorporation of recycled plastics, such as high-density polyethylene (HDPE), was explored to develop more sustainable pavements. The objective of this research was to design and evaluate a replicable methodology to compare traditional asphalt mixtures with mixtures modified with HDPE. To this end, mixtures were prepared using the dry method and subjected to performance tests, including bulk specific gravity (GSB), maximum theoretical specific gravity (Gmm), air void content, and Hamburg wheel tracking test. The results showed that mixtures modified with HDPE exhibited less deformation and maintained porosity levels similar to conventional mixtures, although with a slight decrease in density. It is concluded that the proposed methodology facilitates the integration of recycled plastics into pavements, contributing to waste reduction and improved durability of road infrastructure.